Analysis of Factors Causing Hate Speech on Instagram social media in the Comments Column of Lambe Turah's Instagram Account - Aryati, Yumi; Firdiawan, Khairuh; Ardi, Syaiful; Sumartono, Sumartono (Adabi : Journal of Public Administration and Business, 2024)
Hate speech has become a disturbing social reality. Mistakes in translating the meaning of freedom of opinion become disputes that have legal consequences for the perpetrators. This research aims to determine the factors that cause the emergence and efforts to overcome hate speech. This research uses a qualitative approach and case study method. This research was analyzed using the Melvin Defleur model of individual differences theory which consists of three concepts, namely, selective exposure, selective perception and selective retention. Each other when they are exposed to the mass media. This can happen due to psychological differences, ways of thinking, influence of the surrounding environment, attitudes, values, religion, beliefs and so on. There is the influence of psychological elements that interact with exposure to mass media and produce effects. In this way, there is a strong link between media messages and the response of each individual. In efforts to overcome perpetrators who carry out hate speech on social media, there is a need for education for social media users and more equitable socialization. Because the socialization carried out by the government is currently still limited to certain groups, so those who are not affected by this socialization do not understand that there are ethics that must be understood when using social media so as not to be affected by the ITE Law. There are two ways that can be taken in carrying out socialization, namely socializing the importance of good social media, and it is also important to socialize the ITE Law (Electronic Transaction Interaction) as a guide for social media users so that they do not deal with legal problems.